Pancreatic enzyme supplementation versus placebo for improvement of gastrointestinal symptoms in non-responsive celiac disease: A cross-over randomized controlled trial - Yoosuf, Shakira; Barrett, Caitlin G.; Papamichael, Konstantinos; Madoff, Sarah E.; Kurada, Satya; Hansen, Joshua; Silvester, Jocelyn A.; Therrien, Amelie; Singh, Prashant; Dennis, Melinda; Leffler, Daniel A.; Kelly, Ciaran P. (Frontiers in Medicine, 2023)
Background Pancreatic Exocrine Insufficiency (PEI) is a possible cause of recurrent/persistent symptoms in celiac disease. Although pancreatic enzyme supplementation may be used to treat Non-Responsive Celiac Disease (NRCD) in clinical practice, clinical outcomes are variable and there is limited and low quality evidence to support this practice. The aim of this study was to assess the efficacy of Pancreatic Enzyme Supplements (PES) for improvement of gastrointestinal symptoms in NRCD. Methods Prospective, randomized, placebo-controlled, double-blind, cross-over trial in adults with NRCD examining Celiac Disease-Gastrointestinal Symptom Rating Scale (CeD-GSRS) scores on PES (pancrelipase co-administered with omeprazole) versus placebo (omeprazole only) during a ten-day treatment period. The study was registered under the clinical trials registry (ClinicalTrials.gov number, NCT02475369) on Jun 18, 2015. Results Twelve participants (nine female) were included in the per-protocol analysis; one participant had low fecal elastase-1. Pancrelipase was not associated with significant change in CeD-GSRS compared to placebo(-0.03 vs -0.26; P=0.366). There was a significant decrease in mean values of total CeD-GSRS scores (3.58 vs 2.90, P=0.004), abdominal pain (2.92 vs 2.42, P=0.009) and diarrhea sub-scores (3.44 vs 2.92, P=0.037) during the run-in period with omeprazole. Conclusions In this prospective, cross-over randomized, placebo-controlled study, PES did not improve symptoms in patients with NRCD. It is unclear whether this is a trial effect or related to administration of omeprazole.